Study the effect of green pit viper (Trimeresurus albolabris) venom on platelet morphology - Suphan Soogarun (Chulalongkorn University, 2008)
The incidence of venomous snake bites increases in every year in Thailand, especially by green pit viper. Consequence after the bite is bleeding because of its thrombin-like property. There is a report mentioned that the mean platelet volume was decreased in those who had been bitten by this snake. In this study is to investigate the effect of green pit viper (Trimeresurus albolabris) on platelet volume (MPV), number of platelets and morphology in vitro. The test carried out by washing platelet in phosphate buffer pH 7.2 so as to get rid fibrinogen, and then washed platelets were mixed with green pit viper venom. The mean platelet volume and number of platelets were determined by flowcytometry and its morphology was examined by scanning electron microscope (SEM) respectively. The results showed that the number of platelets were decreased dramatically (216+-101x10[subscript 9] /l and 78.1+-43.4x10[subscript 9] / l P < 0.05) and the MPV was also decreased (8.9+-1.2 fl and 4.8+-1.3fl,P<0.05). The morphology of platelets is smaller than normal which ranges from 1.1-1.2 micrometers. In conclusion, the green pit viper venom can directly effect on platelet morphology especially decreasing platelet volume and numbers.